IMPULSIVE BUYING DITINJAU DARI KONTROL DIRI PADA MAHASISWI PENGGEMAR K-POP DI YOGYAKARTA - Dewi Puspitasari; Siti Hafsah Budi Argiati; Flora Grace Putrianti (Faculty of Psychology Sunan Gunung Djati Islamic University of Bandung, 2022)
AbstractThis study aims to determine the relationship between self-control and impulsive buying of female K-Pop fans. The subjects of this study were female K-Pop fans who joined the